CHAIN SMOKING : LINKING VIRGINIA'S AND BARBADOS' COMMERCIAL TOBACCO PRODUCTION - Tolar, Elizabeth Brooke (East Carolina University, 2010)
The purpose of this thesis is to examine the commercial tobacco production of Virginia and Barbados and explore the connections between them. The economic activities, especially tobacco production, that developed altered England's New World objectives and provided a model for future English colonies in the Americas. This study utilizes colonial records, contemporary accounts, and early histories as well as a wide range of secondary studies of Virginia, Barbados, the English Empire and the Atlantic World.    Early English New World explorers hoped to acquire wealth and glory similar to sixteenth-century Spanish conquistadores. After discovering that Newfoundland, modern-day North Carolina, and Virginia did not offer vast gold-filled mines or passages to the East Indies, the English shifted their New World objective from discovering precious metals or elusive Northwest passages to commercial agriculture. The Jamestown colonists adopted commercial agriculture after failing to discover ready-made wealth in the Virginia interior. Jamestown's successful commercial tobacco production, however, encouraged colonists in future endeavors, including Barbados, to immediately adopt agricultural cultivation. While Barbados eventually proved more suitable for sugar cultivation, Barbadians initially adopted tobacco. Studying Barbados' early attempts at tobacco production provides the perfect opportunity to emphasize Jamestown's influence on England's successive colonies.    While various historians have studied the island's history, they have focused overwhelmingly on the island's lucrative sugar years instead of the less glamorous tobacco era. Even though Barbadians established a colony based on tobacco exports, very few primary sources exist concerning the island's initial years, and tobacco profits never rivaled those of sugar. This thesis will discuss the historiography of both Jamestown and Barbados before illustrating the connections between the two colonies' commercial tobacco cultivation.
Keywords: History, General; Tobacco industry--Virginia--Jamestown Island--History--17th century; Tobacco industry--Barbados--History--17th century; Jamestown Island (Va.)--History--17th century; Barbados--History--17th century